Nitrosyl- versus nitroxyl-cobalamin? - Polaczek, Justyna; Orzel, Lukasz; Stochel, Grazyna; van Eldik, Rudi (Journal of Biological Inorganic Chemistry, 2019)
The Commentary is in answer to the comment of a reader that objected against the use of the term ‘nitroxylcobalamin’ in two recent reports in JBC from our group. We use this opportunity to explain to the reader where this terminology originated from.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Cobalamin; Metal porphyrins; Nitric oxide; Nitrosyl; Nitroxyl; Non-heme complexes